2006
DOI: 10.1080/08035250500477545
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusions in the neonate

Abstract: Congenital pleural effusions usually occur as hydrops or congenital chylothorax. Traumatic (iatrogenic) are the most frequent acquired pleural effusions in a tertiary NICU. Pleural effusions after intra-thoracic surgery are mainly chylothoraces. Non-iatrogenic acquired pleural effusions are associated to several clinical conditions, and mortality is usually associated to the underlying condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 18 publications
6
49
0
1
Order By: Relevance
“…A review of literature found a rate of diagnosis of 1 in 7000 to 1 in 10 000. [7][8][9] In our cohort the incidence was approximately 1 in 5800 live births. There is a suggestion that more infants are being diagnosed with this condition as compared with previously reported literature, mainly due to increase in complex cardiac surgeries in this population.…”
Section: Discussionmentioning
confidence: 66%
“…A review of literature found a rate of diagnosis of 1 in 7000 to 1 in 10 000. [7][8][9] In our cohort the incidence was approximately 1 in 5800 live births. There is a suggestion that more infants are being diagnosed with this condition as compared with previously reported literature, mainly due to increase in complex cardiac surgeries in this population.…”
Section: Discussionmentioning
confidence: 66%
“…71 Idiopathic chylothorax including congenital chylothorax is the third most common in the neonate, and is the most frequent cause of pleural effusion. 72 Congenital chylothorax is more frequent in males (2:1) and on the right side of the thorax. Thoracotomies have shown that the thoracic duct is normal in most of the afflicted babies, and occasionally generalized oozing is described.…”
Section: Chylous Pleural Effusionsmentioning
confidence: 99%
“…64,73 It may be isolated or part of a larger group of lymphatic abnormalities and it has also been associated with Turner's, Down and the Noonan syndromes. 64 Familial congenital chylothorax has been reported in both males 72 and females. 74 The fourth chylothorax category is "other disorders" (e.g., lymphangioleiomyomatosis, tuberculosis, sarcoidosis, KS).…”
Section: Chylous Pleural Effusionsmentioning
confidence: 99%
“…Antibiotics should be given until an infectious etiology has been excluded. [911] Antenatally diagnosed pleural effusions, particularly if present prior to 32 weeks gestation, have a mortality rate as high as 55%. [1213] Bilateral pleural effusions are frequently associated with pulmonary hypoplasia.…”
Section: Discussionmentioning
confidence: 99%